2002
DOI: 10.1128/iai.70.6.2820-2827.2002
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Antigen-Specific Immunoglobulin G Subclasses in Response to Conserved and PolymorphicPlasmodium falciparumAntigens in an In Vitro Model

Abstract: Cytophilic antibodies (Abs) play a critical role in protection against Plasmodium falciparum blood stages, yet little is known about the parameters regulating production of these Abs. We used an in vitro culture system to study the subclass distribution of antigen (Ag)-specific immunoglobulin G (IgG) produced by peripheral blood mononuclear cells (PBMCs) from individuals exposed to P. falciparum or unexposed individuals. PBMCs, cultivated with or without cytokines and exogenous CD40/CD40L signals, were stimula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
26
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 46 publications
1
26
0
Order By: Relevance
“…The preferential induction of IgG3 responses to various P. falciparum asexual-stage antigens, including merozoite surface protein 1 (MSP-1), -2, and -3 and par- asite glycosylphosphatidylinositols, is a well-described phenomenon (8,12,17,45). This preference seems to be associated with the degree of polymorphism associated with the target antigen or epitope thereof, an observation with which in vitro antibody induction assays are largely concordant (19). The prominence of IgG2 that we observed in the adults' anti-VSA antibody profile deserves further comment, since the role of IgG2 antibodies with specificity for plasmodial antigens remains a subject of some controversy.…”
Section: Discussionmentioning
confidence: 79%
“…The preferential induction of IgG3 responses to various P. falciparum asexual-stage antigens, including merozoite surface protein 1 (MSP-1), -2, and -3 and par- asite glycosylphosphatidylinositols, is a well-described phenomenon (8,12,17,45). This preference seems to be associated with the degree of polymorphism associated with the target antigen or epitope thereof, an observation with which in vitro antibody induction assays are largely concordant (19). The prominence of IgG2 that we observed in the adults' anti-VSA antibody profile deserves further comment, since the role of IgG2 antibodies with specificity for plasmodial antigens remains a subject of some controversy.…”
Section: Discussionmentioning
confidence: 79%
“…Polarized IgG1 responses are also reported for Pf155/RESA (17), crude schizont lysate (33), RAP-1 (44), and MSP-6 (50), while IgG3 responses are seen for a polymorphic C-terminal region (block 2) of MSP-1 (11), MSP-3 (11, 31), MSP-4 (51), and MSP-7 (50). A crucial role for antigens per se in driving these patterns of subclass switching has been confirmed experimentally both in vitro with human B cells (21) and in a mouse model where different recombinant P. falciparum antigens-expressed with the same fusion protein tag and administered with the same adjuvant-induced very different IgG subclasses (47). This raises the important question of whether there are intrinsic features of individual malarial antigens which influence their interactions with antigenpresenting cells, T cells, or B cells, leading to the preferential 19 -or AMA-1-specific IgG1 inhibited the simultaneous generation of IgG3 responses to MSP-2, then significantly less than 25% of sera would give ODs above the median for both.…”
Section: Discussionmentioning
confidence: 90%
“…It is unclear whether individuals have a bias toward producing a specific subclass regardless of the antigen or if instead the IgG subclass response is generated independently for each antigen and how this relates to protective immunity. While factors determining subclass responses to antigens are not clearly defined, antigen properties, host age, cumulative exposure, and genetic determinants have been linked with the nature of subclass responses (2,4,17,33,34,41,42,47,48). Some studies have suggested that increasing age (and therefore malaria exposure) leads to an increasing polarization of IgG subclass responses to merozoite antigens (41,48).…”
mentioning
confidence: 99%